2017
DOI: 10.4196/kjpp.2017.21.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Participation of central GABAAreceptors in the trigeminal processing of mechanical allodynia in rats

Abstract: Here we investigated the central processing mechanisms of mechanical allodynia and found a direct excitatory link with low-threshold input to nociceptive neurons. Experiments were performed on male Sprague-Dawley rats weighing 230-280 g. Subcutaneous injection of interleukin 1 beta (IL-1β) (1 ng/10 µL) was used to produce mechanical allodynia and thermal hyperalgesia. Intracisternal administration of bicuculline, a gamma aminobutyric acid A (GABAA) receptor antagonist, produced mechanical allodynia in the orof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is exactly opposite to what is expected from the action of bicuculline, a GABA A receptor antagonist, which previously has been shown to produce mechanical allodynia when given intrathecally in naïve animal [94]. However, the same drug given via the same route in an inflammatory condition produced opposite (anti-allodynic) paradoxical effect [93]. The anti-allodynic effect observed after intrathecal administration of bicuculline in inflammatory condition also contrasts to what has previously been reported where the study reported that bicuculline administration enhanced formalin induced pain behavior [95].…”
Section: Therapies Targeting Central Nociceptive Circuit Dysfunctionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is exactly opposite to what is expected from the action of bicuculline, a GABA A receptor antagonist, which previously has been shown to produce mechanical allodynia when given intrathecally in naïve animal [94]. However, the same drug given via the same route in an inflammatory condition produced opposite (anti-allodynic) paradoxical effect [93]. The anti-allodynic effect observed after intrathecal administration of bicuculline in inflammatory condition also contrasts to what has previously been reported where the study reported that bicuculline administration enhanced formalin induced pain behavior [95].…”
Section: Therapies Targeting Central Nociceptive Circuit Dysfunctionmentioning
confidence: 87%
“…Even though positive modulation of the GABAA receptor α6 subunit has shown anti-allodynic effect, modulation of GABA A receptor either by its selective antagonist bicuculline or agonist muscimol did not show straightforward effect. In a naive rat, intracisternal administration of bicuculline produced mechanical allodynia while in an inflammatory pain models prepared by subcutaneous injection of interleukin 1 beta (IL-1β), the intracisternal administration of bicuculline produced anti-allodynic effect [93]. It is exactly opposite to what is expected from the action of bicuculline, a GABA A receptor antagonist, which previously has been shown to produce mechanical allodynia when given intrathecally in naïve animal [94].…”
Section: Therapies Targeting Central Nociceptive Circuit Dysfunctionmentioning
confidence: 99%
“…Despite the low concentrations of the bumetanide through the central nervous system following systemic administration (Kaila, Price, Payne, Puskarjov, & Voipio, 2014), recent studies indicated that bumetanide is able to control some aspects of neurological and neuropsychological disorders such as epilepsy (Gharaylou et al, 2019), schizophrenia (Rahmanzadeh et al, 2017), autism (James, Gales, & Gales, 2019) and Parkinson disease (Damier, Hammond, & Ben-Ari, 2016). Previous studies have shown that in animal models of spinal cord injury, the use of bumtanide reduces allodynia and hyperalgesia (Kim et al, 2017;Mòdol et al, 2015;Pitcher, Price, Entrena, & Cervero, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All behavioral tests were conducted between 0700 and 1800 hours. The withdrawal behavioral responses produced by 10 successive trials of a ramp of air-puff pressure (4 sec of duration, 10 sec of interval) were examined as described previously [ 17 18 19 20 ]. The intensity of the air-puff pressure was controlled by a pneumatic pump module (BH2 System; Harvard Apparatus, MA).…”
Section: Methodsmentioning
confidence: 99%